2023
DOI: 10.3390/foods12173320
|View full text |Cite
|
Sign up to set email alerts
|

Walnut Flour as an Ingredient for Producing Low-Carbohydrate Bread: Physicochemical, Sensory, and Spectroscopic Characteristics

Monika Wójcik,
Dariusz Dziki,
Arkadiusz Matwijczuk
et al.

Abstract: Walnut flour (WF) is a nutrient-rich source that can be used as an alternative for individuals on a gluten-free diet. This study aimed to assess the physical, chemical, and sensory changes in low-carbohydrate bread when supplemented with WF. Molecular-level changes were also examined using ATR-FTIR spectra. The bread recipe, containing buckwheat and flaxseed, was enriched with WF at levels ranging from 5% to 20%. The addition of WF resulted in increased loaf volume and decreased baking loss. Enriched bread sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
1
0
0
Order By: Relevance
“…Samples with a higher share of WSF were characterized by a lower volume at the level of 1.46 g•cm −3 but comparable to the control bread (1.45 g•cm −3 ). According to our previous research, the addition of poppy or walnut flour to low-carbohydrate, gluten-free bread resulted in an increase in volume [31,32]. In the present studies, no decrease in this parameter was observed compared to the volume of control bread.…”
Section: Basic Properties Of Low-carbohydrate Bread With Different Am...supporting
confidence: 57%
“…Samples with a higher share of WSF were characterized by a lower volume at the level of 1.46 g•cm −3 but comparable to the control bread (1.45 g•cm −3 ). According to our previous research, the addition of poppy or walnut flour to low-carbohydrate, gluten-free bread resulted in an increase in volume [31,32]. In the present studies, no decrease in this parameter was observed compared to the volume of control bread.…”
Section: Basic Properties Of Low-carbohydrate Bread With Different Am...supporting
confidence: 57%